Final thoughts on WWI and WWII legislation, recovery, identification and burial of human remains: best practice, challenges, and recommendations - Márquez-Grant, Nicholas; Errickson, David; Morgan, Sarah; Ronner, Eva; Giles, Stephanie B. (Elsevier, 2021)
The ‘WWI and WWII Symposium: Legislation, Recovery, Identification and Burial of Human Remains’, took place on 13th March 2020 (Márquez-Grant and Errickson, 2021). The event was in the form of a round table discussion with participating specialists who focus on the forensic recovery and identification of war casualties, particularly with a focus on Europe. Although the event saw a large amount of knowledge exchange, the discussion went far beyond those who attended the session. As a result, this Special Issue in ‘Forensic Science International’ is aimed at disseminating the discussion to a wider number of individuals while incorporating further views and input from specialists who could not be in attendance on the day.
Keywords: Forensic Archaeology